The old-age trees of the parks-monuments as park and garden art objects a in Ternopil region - Nadiia Oleksiichenko; Svitlana Pidkhovna (Наукові праці Лісівничої академії наук України, 2018)
Parks-monuments of garden art play in the modern life the role of living witnesses of centuries-old traditions. An important task facing parks, memorials of garden and park art objects, is the preservation of natural and artificial park landscapes, monuments of cultural heritage, valuable introduced and old-age trees on their territories. Detection of the latter, determining their vital and sanitary condition is an important criterion in the complex assessment of the territory for the development of projects for the maintenance and rational use of park-monuments of garden art. The object of the research was the age-old trees of the monuments park-park art of Ternopil region. The subject of research - the vital and aesthetic state of the old -age unique trees in park-monuments of garden art. The purpose of the research was to assess the vital and aesthetic state of the unique trees of the park-monuments of landscape architecture of the Ternopil region and to develop the recommendations for their preservation. The old-age trees in the park-monuments of landscape garden art of the Ternopil region are represented by 30 species and two cultivars (Fagus sylvatica L.‘Atropunicea’ West. і Stypholobium japonicum Schott. ‘Pendula’), most of which (24 species) belong to the Department of Angiospermae. The old-age introducents were found on the territory of eight parks (Bilche-Zolotetskiy, Zalishchytskiy, Raivskiy, Skala-Podilskiy, Plotytskiy, Koropetskiy, Hrymailivskiy parks and in the remains of the park in Mlynysky village). During inventory studies a comprehensive assessment of five old -age trees that have the status of botanical monuments of nature (old-age trees with significant cultural and historic significance and strict conservation regimes) has been carried out and are growing in the Rayivskiy and Zalishchytskiy parks, the sanitary condition has been characterized and their taxonomic and biometric indices. On these objects, old-age trees-introdents (Gymnocladus dioicus (L.) C. Koch) – 130 years old and Stypholobium japonicum Schott. ‘Pendula’- age 150 years old) have been identified. Analyzing the retrospective development of the park area, it can be argued that the trees discovered are among the last unique trees that have survived since the creation of the park and have a biological, scientific, historical, cultural and aesthetic value associated with a significant age and species rarity. It is expedient to take night natural monuments of local importance under the state protection . According to the results of the assessment of the vital and aesthetic state of the prominent trees, a number of organizational and technological measures for their treatment, conservation and rational use have been proposed (creation of the map of the geospatial location of the trees, the organization of measures to reduce the recreational pressure within the area of the projection of the crown, the establishment of information nameplates, carrying out of sanitary measures on diseases affected by age trees on the basis of modern ecologically sound technologies, incl. and methods of arboretics).